Thymoquinone suppression of the human hepatocellular carcinoma cell growth involves inhibition of IL-8 expression, elevated levels of TRAIL receptors, oxidative stress and apoptosis - Ashour, Abdelkader Elbadawy Abbas; Abd-Allah, Adel R. A.; Korashy, Hesham M.; Attia, Sabry M.; Alzahrani, Abderlrahman Z.; Saquib, Quaiser; Bakheet, Saleh A.; Abdel-Hamied, Hala E. (Springer US, 2014)
Hepatocellular carcinoma (HCC) is the fourth most common solid tumor worldwide. The chemokine interleukin-8 (IL-8) is overexpressed in HCC and is a potential target for therapy. Although the transcription factor NF-κB regulates IL-8 expression, and while thymoquinone (TQ; the most bioactive constituent of black seed oil) inhibits NF-κB activity, the precise mechanisms by which TQ regulates IL-8 and cancer cell growth remain to be clarified. Here, we report that TQ inhibited growth of HCC cells in a dose- and time-dependent manner, caused G2M cell cycle arrest, and stimulated apoptosis. Apoptosis was substantiated by activation of caspase-3 and -9, as well as cleavage of poly(ADP-ribose)polymerase. TQ treatments inhibited expression of NF-κB and suppressed IL-8 and its receptors. TQ treatments caused increased levels of reactive oxygen species (ROS) and mRNAs of oxidative stress-related genes, NQO1 and HO-1. Pretreatment of HepG2 cells with N-acetylcysteine, a scavenger of ROS, prevented TQ-induced cell death. TQ treatment stimulated mRNA expression of pro-apoptotic Bcl-xS and TRAIL death receptors, and inhibited expression of the anti-apoptotic gene Bcl-2. TQ enhanced TRAIL-induced death of HepG2 cells, in part by up-regulating TRAIL death receptors, inhibiting NF-κB and IL-8 and stimulating apoptosis. Altogether, these findings provide insights into the pleiotropic molecular mechanisms of TQ-dependent suppression of HCC cell growth and underscore potential of this compound as anti-HCC drug.